KEBIJAKAN FORMULASI TERHADAP PENIRUAN TAMPILAN WEBSITE DI INDONESIA - Ajeng Widya Paramita (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
One of the implications of information technology to which attention is currently paid is its impact on the existence of Intellectual Property Right. One of the crimes committed to the right of intellectual property is the illegal imitation of presentation on web page of sites belonging to others popularly known as Offense against Intellectual Property. Based on the background above, the problems discussed in this study are the formulation of criminal act and the policy of formulation in the future system of sanction imposed upon the imitation of presentation of website in Indonesia. Normative method based on the regulations of laws related to the crime of the imitation of presentation of website in Indonesia was used in the present study. The results of the study showed that the elements of the formulation of criminal act of the imitation of presentation of website in Indonesia are subjective and objective ones. The policy of the formulation of the system of criminal sanction imposed upon the limitation of presentation of website in Indonesia applies the type of cumulative criminal threaten which includes two types of punishment. The formulation is a 2 (two) year imprisonment and/or a maximum spesific fine of Rp. 150.000.000,00 (one hundred fifty thousand rupiahs), based on Article 72 Clause (6) jo Article 24 of the Criminal Law.